A review of the characteristics of nanoparticles in the urban atmosphere and the prospects for developing regulatory controls - Kumar, Prashant; Robins, Alan; Vardoulakis, Sotiris; Britter, Rex (Atmospheric environment (1994), 2010)
The likely health and environmental implications associated with atmospheric nanoparticles have prompted considerable recent research activity. Knowledge of the characteristics of these particles has improved considerably due to an ever growing interest in the scientific community, though not yet sufficient to enable regulatory decision making on a particle number basis. This review synthesizes the existing knowledge of nanoparticles in the urban atmosphere, highlights recent advances in our understanding and discusses research priorities and emerging aspects of the subject. The article begins by describing the characteristics of the particles and in doing so treats their formation, chemical composition and number concentrations, as well as the role of removal mechanisms of various kinds. This is followed by an overview of emerging classes of nanoparticles (i.e. manufactured and bio-fuel derived), together with a brief discussion of other sources. The subsequent section provides a comprehensive review of the working principles, capabilities and limitations of the main classes of advanced instrumentation that are currently deployed to measure number and size distributions of nanoparticles in the atmosphere. A further section focuses on the dispersion modelling of nanoparticles and associated challenges. Recent toxicological and epidemiological studies are reviewed so as to highlight both current trends and the research needs relating to exposure to particles and the associated health implications. The review then addresses regulatory concerns by providing an historical perspective of recent developments together with the associated challenges involved in the control of airborne nanoparticle concentrations. The article concludes with a critical discussion of the topic areas covered.